A Octa- Rectangular Slot Array based Patch Antenna for Multiband Applications. (October 2019) - Karthikeyan, V.; Raveendra, Muddineni; Hemasri, Challa; Praneetha Reddy, Male; Harshitha, B.
Abstract: In this paper, a octa rectangular-slot array based patch antenna for multiband applications has been proposed. The operating frequency range of proposed antenna is 11-21.817 GHz in the X, Ku and K bands. This antenna designed with octa rectangular shaped slots on rectangular patch antenna. The FR4 (Flame Retardant)substrate material is used in this antenna, which has relative permittivity 3.66, relative permeability 1, loss tangent 0.0018 and thickness of 2mm.The design has been stimulated by using HFSS software. The performance of the antenna is analysed with the help of characteristics of return loss, VSWR, bandwidth, gain and directivity at each band. It gives resonance frequencies at 11.1GHz, 14.3GHz, 16.1GHz, 17.5GHz, 19.3 GHz and 20.3GHz.